Pengaruh Leadership Coaching dan Motivasi Terhadap Kinerja Dengan Komitmen Organisasi Sebagai Mediator pada Satuan Kerja Pelayanan Markas Polda Jambi - Hutapea, Lamhot Hutapea; Edward, Edward; Wediawati, Besse (Siber Nusantara Publisher, 2023)
The purpose of this study was to determine and analyze the influence of Leadership Coaching and motivation on performance through organizational commitment as a mediator in the Jambi Regional Police Yanma Unit. The analysis tool used is PLS analysis. The results showed that work motivation, Leadership Coaching, organizational commitment and employee performance at the Jambi Regional Police Yanma Unit were in the good category. Leadership Coaching has a positive and significant effect on organizational commitment to the Jambi Regional Police Yanma Unit. Work motivation has no significant effect on organizational commitment to the Jambi Regional Police Yanma Unit. Leadership Coaching has a positive and significant effect on employee performance at the Jambi Regional Police Yanma Unit. Work motivation has no significant effect on employee performance at the Jambi Regional Police Yanma Unit. Organizational commitment has a positive and significant effect on employee performance at the Jambi Regional Police Yanma Unit. Leadership Coaching has a significant and positive effect on employee performance with organizational commitment as a mediator variable in the Jambi Regional Police Yanma Unit. Work motivation has no significant effect on employee performance with organizational commitment as a mediator variable